The impact of maternal asthma during pregnancy on offspring retinal microvascular structure and its relationship to placental growth factor production in utero. (14th May 2020) - Jones, Ailee R.; Tuckwell, Christine; Wright, Ian M. R.; Morrison, Janna L.; Kandasamy, Yogavijayan; Wittwer, Melanie R.; Arstall, Margaret A.; Stark, Michael J.; Davies, Michael; Hurst, Cameron; Okano, Satomi; Clifton, Vicki L.
Abstract: Asthma is a common chronic disease in pregnancy that affects placental function and fetal growth and associated with cardio‐metabolic disorders in the offspring but the mechanisms are unknown. This study explored whether maternal asthma in pregnancy is associated with the development of offspring microvascular structure and whether it was related to biomarkers of angiogenesis in utero. Children aged 4 to 6 years, born to either asthmatic mothers (n = 38) or healthy controls (n = 25), had their retinal microvascular structure examined. Maternal plasma PlGF concentrations at 18 and 36 weeks' gestation were measured. There was a significant global difference in all retinal microvascular measures between children of asthmatic mothers relative to controls and increased retinal venular tortuosity in children born to asthmatic mothers (7.1 (95% CI 0.7‐13.5); P = .031). A rise in plasma PlGF from 18 to 36 weeks' gestation was observed in the control population which was significantly lower in the asthma group by 190.9 pg/mL. PlGF concentrations were correlated with microvascular structure including arteriolar branching and venular tortuosity. These exploratory findings indicate that exposure to maternal asthma during pregnancy is associated with persistent changes in microvascular structure in childhood that may be driven by alterations to angiogenic mechanisms in utero.